Breast tuberculosis - Celedonio, Magnolia (2015)
OBJECTIVE: To present three cases of breast tuberculosis. MATERIALS AND METHODS: The medical records of three patients with breast tuberculosis clinic and histologically diagnosed in the Health Center between 1998 and 1999. Progress was revised RESULTS: The three cases were female patients aged between 27 and 31 years. The growth was varied flogótica and consistency, without axillary lymph node biopsy diagnosis of chronic granulomatous inflammatory process was consistent with tuberculous etiology. All had a favorable evolution and surgical aftercare tuberculosis. CONCLUSION: We report three cases of breast tuberculosis where no objective extramammary involvement.